2005
DOI: 10.4095/221042
|View full text |Cite
|
Sign up to set email alerts
|

Well-test analysis for gas hydrate reservoirs: examination of parameters suggested by conventional analysis for the JAPEX/JNOC/GSC et al. Mallik 5L-38 gas hydrate production research well

Abstract: In the Mallik 2002 Gas Hydrate Production Research Well Program, formation tests with a Modular Formation Dynamics Tester (MDT)TM tool were conducted and the test results were analyzed using conventional pressure-transient test-analysis methods. The reliability of the reservoir-parameter estimates, however, is uncertain because of the abrupt change in gas hydrate saturation associated with gas hydrate dissociation during the tests. To investigate the applicability of these methods, the bottomhole-pressure re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…This is because the shut-in period is devoid of rate fluctuations suffered by a typical flow period. Kurihara et al (2005Kurihara et al ( , 2008 have demonstrated the application of conventional welltest analysis techniques to analysis of MDT tests in hydrate reservoirs and has explored its limitations. We matched the pressure of the first shut-in period by using the FAST WellTest software package of Fekete that employs an analytical solution of the diffusivity equation with various boundary conditions.…”
Section: Match Of the Initial Flow And Shut-inmentioning
confidence: 98%
“…This is because the shut-in period is devoid of rate fluctuations suffered by a typical flow period. Kurihara et al (2005Kurihara et al ( , 2008 have demonstrated the application of conventional welltest analysis techniques to analysis of MDT tests in hydrate reservoirs and has explored its limitations. We matched the pressure of the first shut-in period by using the FAST WellTest software package of Fekete that employs an analytical solution of the diffusivity equation with various boundary conditions.…”
Section: Match Of the Initial Flow And Shut-inmentioning
confidence: 98%
“…The long-term predictions of production indicated the advantage of depressurization (over thermal stimulation) as a viable method for hydrate dissociation and commercial gas production, and further demonstrated the superiority of methods combining depressurization and thermal stimulation (Moridis et al, 2005b;Kurihara et al, 2005c). The substantial differences in the long-term predictions of the models were not unexpected (given the short duration of the experiment and the almost chaotic behavior of gas wells immediately after the initiation of production), and served to underscore the need for longer-term tests.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical developments on well testing of GH reservoirs have received some attention over the past few years. In one of such developments, Kurihara et al (2005) examined the applicability of conventional PTA techniques to interpretation of MDT results in hydrate reservoirs. They simulated flow and shut-in periods similar to those at the Mallik 2002 test, and then applied the conventional PTA techniques for analysis of the synthetically generated pressures.…”
Section: Well Testing and Interpretation Issuesmentioning
confidence: 99%
“…The results indicated that the effective permeability found from application of the conventional PTA techniques, was in close agreement with an average effective permeability over the dissociation zone. In their comprehensive work, Kurihara et al (2005) examined the validity of the assumptions used in conventional PTA techniques. These are discussed under "Theoretical Developments.…”
Section: Well Testing and Interpretation Issuesmentioning
confidence: 99%
See 1 more Smart Citation